Theorising Mental Disorder: A Sociological Approach - Baltrušaitytė, Giedrė (Sociologija. Mintis ir veiksmas, 2003)
The article introduces and critically discusses major sociological ideas on the concept of mental disorder. Starting with Parsonian ‘sick role’ and illness as deviance, the article proceeds with labelling theory and further on with Foucault’s conceptualisation of madness as an opposition to reason. Conflict approach on mental disorder is presented as based on belief that structural inequality is one of the major sources of suffering in modern society. Constructivist critique makes an emphasis on the fragile, incoherent nature of the categories of mental disorder. Finally, the introduction of the concept of emotion into sociology of mental disorder is presented as providing new analytical tool to account for the ways mind and body are linked in a disordered condition. Sociological perspective explores dominant concepts of mental disorder and offers different ways of thinking about mental phenomena, while locating them within a broader social context and an analysis of social relations. This helps to understand better the social organisation of mental health care, patterns of psychiatric practice and the process of becoming mentally disordered.